ANTECEDENTS OF TEAM PERFORMANCE: EXPLORING THE MEDIATING ROLE OF TRUST IN COACH AMONG MALAYSIAN SPORTS PLAYERS - Mussarrat, Ayesha (CENTRAL ASIA AND THE CAUCASUS, 2022)
The study’s primary purpose is to examine the relationship between team tenure, team leadership, justice, coach trust, and team performance. Additionally, this research examined the mediating role of faith in coaches. A cross-sectional research design was used to keep the study’s objectives in mind. Simple random sampling was used to acquire data from football and hockey players. The study’s usable response rate was 70.92%. PLS-SEM was used to analyse the obtained data. The study’s findings revealed the existence of a strong association between team tenure, team leadership, coach trust, and team performance. Additionally, the mediating function of faith in the relationship between tenure, leadership, and performance is endorsed. These findings are beneficial for both sports industry policymakers and academics.